Campos Verdes-GO and the garimpo de esmeraldas: territory, local development and deterritoriality (Research, Society and Development, 2022)
The objective was to analyze the discovery of emeralds, the occupation of the territory and the emergence of the city of Campos Verdes, marked by local economic development, at the height of emerald exploration and later, its decay and the emptying of the city. The theoretical framework of this research was based on the concepts of territory and deterritoriality and its dynamics, as well as that of local development. Thus, descriptive research of qualitative character and field research was conducted, with the application of questionnaires, to observe how the populations of these localities historically perceive the territory and local economic development – or not – from the mining. The results showed that the prospector, due to the temporal nature of the exploration mines, breaks with the logic of fixation in the territory, generating emptying of cities and regions when the mining enters crisis. These processes lead to the questioning of the notion of development associated with mining activity, since it presents a predatory character and high environmental risk, incompatible with sustainable development.